2013
DOI: 10.4028/www.scientific.net/amr.853.79
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nano-branched Coaxial Polyaniline / Polyvinylidene Fluoride Fibers via Electrospinning for Strain Sensor

Abstract: Soft conductive elastomer materials have wide potential applications in material science and electronic engineering. Through electrospinning and in-situ polymerization, a kind of well-organized coaxial polyaniline/polyvinylidence fluoride (PANI/PVDF) microfibers with conductivity about 0.6 S/cm were fabricated, which combined the advantages of conducting polymer and elastic material. It is found that the resistance of the fibers was changed with the curvature variation. The results indicate that the PANI/PVDF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Several types of electrospun PANI nanofiber based sensors have been developed lately. Recent reports include the electrospun nanofiber of graphene/PANI/PS for the detection of Pb and Cd ions [165], PANI/SnO 2 for H 2 gas sensing [166], multiple detections using PANI/PCL [167], PANI/polyamide 66 for colorimetric sensing [168], PANI/poly(ethylene oxide) gas sensor [169], PANI/ZnO for chemiresistor sensor [170], PANI/PLA to sense alcohol vapors of increasing molecular size [171], PANI/polyvinylidene fluoride as strain sensor [172], high sensitivity gas sensors based on PANI/PMMA [173], PANI/fibroin microfibrous mat as reactive sensor [174], and PANI/polyamide 6/TiO 2 nanofibers for ammonia sensor [175,176].…”
Section: Applications Of Electrospun Pani Nanofibersmentioning
confidence: 99%
“…Several types of electrospun PANI nanofiber based sensors have been developed lately. Recent reports include the electrospun nanofiber of graphene/PANI/PS for the detection of Pb and Cd ions [165], PANI/SnO 2 for H 2 gas sensing [166], multiple detections using PANI/PCL [167], PANI/polyamide 66 for colorimetric sensing [168], PANI/poly(ethylene oxide) gas sensor [169], PANI/ZnO for chemiresistor sensor [170], PANI/PLA to sense alcohol vapors of increasing molecular size [171], PANI/polyvinylidene fluoride as strain sensor [172], high sensitivity gas sensors based on PANI/PMMA [173], PANI/fibroin microfibrous mat as reactive sensor [174], and PANI/polyamide 6/TiO 2 nanofibers for ammonia sensor [175,176].…”
Section: Applications Of Electrospun Pani Nanofibersmentioning
confidence: 99%
“…Coaxial electrospun fibers have been shown to be useful in gene delivery [9], drug delivery [10], bioactive molecules delivery [11] [12] and sensors [13], for example.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the coating of PANI on functional MWCNT reduced its entanglement and enhanced the interfacial interaction between the nano fillers and TPU, leading to improved strain sensitivity. Other investigators [9][10][11] also showed that PANI composites have superior strain sensitive properties.…”
Section: Introductionmentioning
confidence: 95%